How Alluring Are Dark Personalities? The Dark Triad and Attractiveness in Speed Dating. Issue 2 (11th January 2016) - Jauk, Emanuel; Neubauer, Aljoscha C.; Mairunteregger, Thomas; Pemp, Stephanie; Sieber, Katharina P.; Rauthmann, John F.
Abstract: Dark Triad traits (narcissism, psychopathy, and Machiavellianism) are linked to the pursuit of short‐term mating strategies, but they may have differential effects on actual mating success in naturalistic scenarios: Narcissism may be a facilitator for men's short‐term mating success, while Machiavellianism and psychopathy may be detrimental. To date, little is known about the attractiveness of Dark Triad traits in women. In a speed‐dating study, we assessed participants' Dark Triad traits, Big Five personality traits, and physical attractiveness in N = 90 heterosexual individuals (46 women and 44 men). Each participant rated each partner's mate appeal for short‐ and long‐term relationships. Across both sexes, narcissism was positively associated with mate appeal for short‐ and long‐term relationships. Further analyses indicated that these associations were due to the shared variance among narcissism and extraversion in men and narcissism and physical attractiveness in women, respectively. In women, psychopathy was also positively associated with mate appeal for short‐term relationships. Regarding mating preferences, narcissism was found to involve greater choosiness in the rating of others' mate appeal (but not actual choices) in men, while psychopathy was associated with greater openness towards short‐term relationships in women. Copyright © 2016 European Association of Personality Psychology